Perros platónicos. Una lectura de la imagen del perro en la República (2021)
Plato’s Republic is built up around a multiplicity of images, even around the philosophical issue of image itself. In this article we would like to inquire about the image of the dog, and its savage counterpart, the wolf, in Plato’s main work. The dog plays a fundamental role in a major issue of the Republic, education. In order to achieve this, first we will investigate the anthropological function of dogs in Ancient Greece, and then we will look for its function inside the Republic.